Understanding extreme quasar optical variability with CRTS – II. Changing-state quasars. Issue 4 (20th November 2019) - Graham, Matthew J; Ross, Nicholas P; Stern, Daniel; Drake, Andrew J; McKernan, Barry; Ford, K E Saavik; Djorgovski, S G; Mahabal, Ashish A; Glikman, Eilat; Larson, Steve; Christensen, Eric
ABSTRACT: We present the results of a systematic search for quasars in the Catalina Real-time Transient Survey exhibiting both strong photometric variability and spectroscopic variability over a decadal baseline. We identify 111 sources with specific patterns of optical and mid-infrared photometric behaviour and a defined spectroscopic change. These 'changing-state' quasars (CSQs) form a higher luminosity sample to complement existing sets of 'changing-look' AGNs and quasars in the literature. The CSQs (by selection) exhibit larger photometric variability than the changing-look quasars (CLQs). The spectroscopic variability is marginally stronger in the CSQs than CLQs as defined by the change in H β/[O III ] ratio. We find 48 sources with declining H β flux and 63 sources with increasing H β flux, and discover 8 sources with z > 0.8, further extending the redshift arm. Our CSQ sample compares to the literature CLQ objects in similar distributions of H β flux ratios and differential Eddington ratios between high (bright) and low (dim) states. Taken as a whole, we find that this population of extreme varying quasars is associated with changes in the Eddington ratio and the time-scales imply cooling/heating fronts propagating through the disc.